PERLINDUNGAN HUKUM BAGI KONSUMEN YANG MENGALAMI KERUGIAN BERUPA PENIPUAN MELALUI TRANSAKSI JUAL BELI ONLINE SHOP - Virna Dewi (Justici, 2021)
The development of the times is increasingly fast making technology even faster. With the rapid development of technology, the easier it is for everyone to meet their needs. Internet technology has a huge influence on the world economy. Online businesses that are increasingly in line with technological developments will certainly make it easier for us to meet our needs. This is what business actors take advantage of as their business opportunity, for various types of business, both food and beverage, transportation, clothing and so on. With this development, the e-commerce trend has emerged in the surrounding environment. The existence of these technological developments also provides vigilance for the government, namely by making laws regarding crimes or fraud that may occur in cyberspace. Important issues raised in this study are about how legal protection for consumers who experience losses in the form of fraud through online buying and selling transactions (online shop). In accordance with the field of legal studies, the approach used in this research is juridical normative. The specification used in this research is descriptive analytical. The data collection technique used by the writer is in the form of literature study. As for the results of this study, the current advances in internet technology have encouraged business actors to plunge into e-commerce. However, these advances can be used by business actors to cheat. And there are laws and regulations established by the government to deal with crimes related to violations of internet use that can harm consumers. In fact, there are still many criminal offenses committed by irresponsible business actors. Due to the lack of tight government supervision and inadequate capacity of law enforcement.